Modulation of spectroscopic properties in the YXO4 compounds (where X = V5+, P5+, As5+) doped with Eu3+ ions - Adam Watras; Marta Kardach; Katarzyna Szyszka; Paulina Sobierajska; Aleksandra Bartkowiak; Rafal J. Wiglusz (Optical Materials: X, 2024)
In the present work, a co-precipitation method was employed to prepare nanosized YXO4 (X = V5+, P5+, As5+) doped with Eu3+ ions. The raw nanomaterials have been thermally treated in temperature range between 300 and 1100 °C for 3h. The XRD analysis demonstrated that the powders were single-phase with high crystallite dispersion. The studies focused on investigating the systematic relationship between crystallographic parameters and spectroscopic properties. The average size of the obtained materials was 30 nm for YVO4, 35 nm for YPO4, and 20 nm for YAsO4, respectively.Moreover, the emission and excitation spectra, although typical for Eu3+ ions, demonstrated some degree of variability with calcination temperatures and doping concentration. Thermal luminescence quenching was typical for YPO4 and YAsO4 samples, while for the YVO4 samples, the intensity of emission increased, reaching its maximum at 725 K. To explain this phenomenon, excitation spectra in function of temperature were measured.